2015
DOI: 10.4018/ijirr.2015100104
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Approach for Single Text Document Summarization Using Statistical and Sentiment Features

Abstract: Summarization is a way to represent same information in concise way with equal sense. This can be categorized in two type Abstractive and Extractive type. Our work is focused around Extractive summarization. A generic approach to extractive summarization is to consider sentence as an entity, score each sentence based on some indicative features to ascertain the quality of sentence for inclusion in summary. Sort the sentences on the score and consider top n sentences for summarization. Mostly statistical featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Based on this hypothesis, we are convinced that some specific features also have certain relationship with their contexts. In fact, there are already researches aiming at word sense disambiguation based on contexts . We found that training an embedding model using bigrams as basic units can map bigram feature to fixed length vectors, so that the semantic information of phrase might be captured, and for homographs and polysemy, we treat them as different words when they have different part‐of‐speech.…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…Based on this hypothesis, we are convinced that some specific features also have certain relationship with their contexts. In fact, there are already researches aiming at word sense disambiguation based on contexts . We found that training an embedding model using bigrams as basic units can map bigram feature to fixed length vectors, so that the semantic information of phrase might be captured, and for homographs and polysemy, we treat them as different words when they have different part‐of‐speech.…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…• Sentence position: Many researchers have considered sentence position feature as scoring feature in the document because most important sentences can be seen at the beginning of the document (Babar and Patil, 2015;Ferreira et al, 2013;Yadav and Sharan, 2015). The equation which we are using to calculate the sentence location score is shown in equation 6.…”
Section: Sentence Featurementioning
confidence: 99%
“…Scientific papers and government reports are examples of lengthy texts that frequently explore important topics in -depth and take lot of time to read [11]. Text document summarizing is referred to as summarization process and is crucial component of inform ation retrieval since it reduces big body of information into manageable amounts by choosing most significant sentences and omitting unnecessary ones [12]. Problem of information overload is solved by text summarizing that locates and selects important sentences from documents to create text summaries automatically.…”
Section: Introductionmentioning
confidence: 99%